Association between serum lactate dehydrogenase and frailty among individuals with metabolic syndrome - Chen, Li-Hsiang; Wu, Li-Wei (PloS one, 2021)
While metabolic syndrome (MetS) is associated with frailty, the correlation of serum lactate dehydrogenase (sLDH) and frailty with MetS remain uncertain. To investigate the relationship between sLDH and frail components in the US with MetS. A total of 4,066 participants aged 40–90 years were assessed from the database of the third National Health and Nutrition Examination Survey, 1988–1994. The participants were classified into MetS and non-MetS groups. Multivariate logistic regression analysis with four models were performed to assess the odds ratio (OR) of the divided tertiles of sLDH levels with frailty, and frail components including slow walking (SW), weakness, exhaustion, low physical activity (LPA), and low body weight (LBW). Higher sLDH levels were positively associated with frailty in the MetS group ( p = 0.024) but not in non-MetS group ( p = 0.102). After covariate adjustments, the OR of frailty in the upper two tertiles compared to the lowest tertile and revealed statistical significance ( p < 0.05). Frail components of SW, weakness, exhaustion, and LPA were associated with higher sLDH ( p < 0.05) except for LBW in MetS and non-MetS groups. The results demonstrated the strong association of higher sLDH levels and frailty among US individuals with MetS.